Anti-Inflammatory Activity of Crude Venom Isolated from Parasitoid Wasp, Bracon hebetor Say. (29th October 2017) - Saba, Evelyn; Shafeeq, Tahir; Irfan, Muhammad; Lee, Yuan Yee; Kwon, Hyuk-Woo; Seo, Myung Gi; Park, Sang-Joon; Lee, Kyeong-Yeoll; Rhee, Man Hee
Abstract : Pest control in the agricultural fields, a major concern globally, is currently achieved through chemical or biological methods. Chemical methods, which leave toxic residue in the produce, are less preferred than biological methods. Venoms injected by stings of various wasps that kill the pest is considered as the examples of the biological method. Although several studies have investigated the biological control of pests through these venoms, very few studies have reported the effects of these venoms on mammalian cells. Bracon hebetor, an ectoparasitoid of the order Hymenoptera, is having a paramount importance in parasitizing various lepidopterous larvae including Plodia interpunctella also called as Indianmeal moth (IMM). Since it is biologically controlled by B. hebetor venom, therefore in our study, herein for the first time, we report the anti-inflammatory activities of the venom from B. hebetor (BHV). We developed a septic shock mice model for in vivo anti-inflammatory studies and RAW 264.7 cells for in vitro studies. Our results clearly demonstrate that BHV can dose dependently abrogate the nitric oxide (NO) production and suppress the levels of proinflammatory mediators and cytokines without posing any cytotoxicity via the nuclear factor kappa B (NF- κ B) and mitogen-activated protein kinase (MAPK) pathways.